The Effectiveness of Audio-Visual Memorization Methods on Short Surah Memorization of Grade II Students - Fitri Ayu Sadimo; Yusdin Bin.M Gagaramusu; Dyah Rahmawati; Nashrullah Nashrullah; Ammar Abdullah Joni Guci (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The background of this study is the low memorization ability of students, caused by the use of conventional teaching methods and the lack of engaging learning media. Therefore, an instructional innovation using audiovisual media is needed to improve students’ interest and memorization skills. This study aims to determine the effectiveness of implementing a memorization method through audiovisual media on students’ ability to memorize short surahs in Grade II at SD Al-Khairaat Mamboro. This study employed a quantitative approach using an experimental pre-experimental design with a one-group pretest-posttest format. A total of 27 Grade II students of SD Al-Khairaat Mamboro were selected using a saturated sampling technique. Data were collected through tests (pre-test and post-test), observation, and documentation. The data were analyzed using descriptive and inferential analyses, including normality tests and hypothesis tests (paired-samples t-test or Wilcoxon test). The results showed an improvement in students’ ability to memorize short surahs after the implementation of the audiovisual method. A significant difference between the pre-test and post-test scores evidenced this. Thus, it can be concluded that implementing memorization methods through audiovisual media is effective in improving students’ ability to memorize short surahs in Grade II at SD Al-Khairaat Mamboro.